ANALISIS DAMPAK INSENTIF PAJAK TERHADAP KEBERLANGSUNGAN USAHA PADA UMKM DI KOTA MADIUN - Erica Putri Rahayu; Isharijadi Isharijadi; Liana Vivin Wihartanti (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to determine the knowledge, utilization, application and impact of tax incentives on MSMEs on business continuity. This research was motivated by MSMEs experiencing difficulties with the Covid-19 pandemic. The government provides tax incentive facilities to relieve the community. This tax incentive provides convenience for business actors in carrying out their business activities. This type of research uses descriptive qualitative. The sampling technique used is interactive analysis technique, namely descriptive technique. The samples used were 6 MSMEs including My Optic, Caffe Pool.co, Ishoma, Niored Printing, Photocopy and Print Shops, and the